THE WASSENAAR ARRANGEMENT AND RUSSIAN HIGH-TECH EXPORT - L. S. Revenko; N. S. Revenko (Vestnik MGIMO-Universiteta)
The current military and political situation in the world raises the necessity of use by Russia of all existing tools to counter actions targeted against it. Participation of the country in international export control regimes, including the Wassenaar Arrangement (the WA), is one of these tools. Membership in the WA allows to Russia to maintain its international status, to contribute to strengthening of international stability, to ensure the non-targeting of this forum against the country, to participate in the development of decisions affecting its interests. Participation in the WA is also important from the view of modernizations of Russian economy towards transition to a new technological mode accompanied by emergence of new groups of innovative products and modification of existing ones. Control of crossing the country's borders by dual-use goods and services is one of conditions for carrying out their export. The Wassenaar Arrangement was established in 1995 to replace COCOM in order to contribute to regional and international security and stability. A huge work is carried out within the forum aimed at enhancing control over transfers of conventional weapons and high-tech dual-use goods. Russian export control system fully meets requirements of international export control regime, including the WA, and effectively functions. Export of the controlled goods from Russia or their transfer to foreign individuals and legal entities are possible only on the basis of decisions of the Export control Commission of the Russian Federation. The dilemma between the need to support exporters by reducing administrative barriers and the ensuring security interests of the country gain momentum in current stage of scientific-and-technological advance development.